PENGARUH PENERAPAN E-KINERJA DAN SELF-EFFICACY TERHADAP KINERJA PEGAWAI DENGAN INTEGRITAS SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Sekretariat Jenderal Ombudsman Republik Indonesia) - Bimo Hadisaputro (2022)
This research was conducted using tests through quantitative methods which aimed to determine the effect of implementing e-performance and self-efficacy on employee performance with integrity as a moderating variable carried out at the employees of the Secretariat General of the Ombudsman of the Republic of Indonesia. Respondents in this study were 115 employees, with sampling using the slovin approach formula with an error rate of 5%. The analysis technique used is the path analysis method and data processing is done through SmartPLS 3.0. The results of testing this study were obtained (1) e-performance has a positive and significant effect on the performance of employees of the Secretariat General of the Ombudsman of the Republic of Indonesia. (2) Self-efficacy has a positive and significant effect on the performance of employees of the Secretariat General of the Ombudsman of the Republic of Indonesia. (3) e-performance which is moderated by integrity has no effect and is not significant but still has a positive influence on the performance of the employees of the Secretariat General of the Ombudsman of the Republic of Indonesia. (4) Self-efficacy moderated by integrity does not have a positive and insignificant effect on the performance of the employees of the Secretariat General of the Ombudsman of the Republic of Indonesia. (5) Integrity has a positive and significant effect on the performance of employees of the Secretariat General of the Ombudsman of the Republic of Indonesia.